2011
DOI: 10.1016/j.ultramic.2011.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Design of a hybrid double-sideband/single-sideband (schlieren) objective aperture suitable for electron microscopy

Abstract: A novel design is described for an aperture that blocks a half-plane of the electron diffraction pattern out to a desired scattering angle, and then – except for a narrow support beam – transmits all of the scattered electrons beyond that angle. Our proposed tulip-shaped design is thus a hybrid between the single-sideband (ssb) aperture, which blocks a full half-plane of the diffraction pattern, and the conventional (i.e. fully open) double-sideband (dsb) aperture. The benefits of this hybrid design include th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Although the gold surface of the BPP is highly conductive and held at ground potential, we observed severe charging, possibly as a result of uncompensated surface charges trapped in insulating contaminants on the gold surface. Such insulating contaminants could be diamond-like carbon that might build up under the intense electron radiation [1], gold oxide that might form due to ionization and reactive dissociation of adsorbed water when hit by electrons [10,20], or polymerized hydrocarbons that cover the gold surface [1]. In an attempt to reduce the effect of possible surface charges, we developed a PP goniometer equipped with a gas injection system consisting of metallic nozzles pointing towards the PP chip (Fig.…”
Section: Manipulating the Phase Plate Surface In Situ With A Gas Injementioning
confidence: 99%
See 3 more Smart Citations
“…Although the gold surface of the BPP is highly conductive and held at ground potential, we observed severe charging, possibly as a result of uncompensated surface charges trapped in insulating contaminants on the gold surface. Such insulating contaminants could be diamond-like carbon that might build up under the intense electron radiation [1], gold oxide that might form due to ionization and reactive dissociation of adsorbed water when hit by electrons [10,20], or polymerized hydrocarbons that cover the gold surface [1]. In an attempt to reduce the effect of possible surface charges, we developed a PP goniometer equipped with a gas injection system consisting of metallic nozzles pointing towards the PP chip (Fig.…”
Section: Manipulating the Phase Plate Surface In Situ With A Gas Injementioning
confidence: 99%
“…Ionized argon molecules directly interact with trapped charges on the BPP surface, clean the BPP surface, or even modify the surface structure. It has been observed that sputter cleaning with argon reduces the grain size and creates a more amorphous gold structure [10]. The origin of changes in the Fourier pattern observed after argon injection remains elusive and needs further investigation.…”
Section: Manipulating the Phase Plate Surface In Situ With A Gas Injementioning
confidence: 99%
See 2 more Smart Citations
“…(2) The "Zach" type [14] has an electrode that projects near the axis of the diffraction plane, producing an electrostatic field next to its tip. (3) The "tulip" type [15] has a small, central semi-circular element that blocks a range of the lowest spatial frequencies -only on one side of the diffraction plane -thus creating a single-sideband type of contrast transfer for these frequencies, while retaining conventional double-sideband imaging for the higher frequencies.…”
mentioning
confidence: 99%